2017
DOI: 10.4149/av_2017_02_04
|View full text |Cite
|
Sign up to set email alerts
|

Combination of H120 and 1/96 avian infectious bronchitis virus vaccine strains protect chickens against challenge with IS/1494/06 (variant 2)-like infectious bronchitis virus

Abstract: Avian infectious bronchitis (IB) is a worldwide chicken disease, caused by avian infectious bronchitis virus (IBV) which infects all commercial poultry lines. The present study was done to evaluate protection caused by two different serotype vaccines (Massachusetts and 793/B) in order to evaluate protection against challenge with IS/1494/06-like virus (variant 2-like virus), which is prevalent in the Middle East. SPF chickens were divided into four groups (n = 20). First and second group as negative control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Varinat 2 viruses are still among the main strains of Jordan, Egypt, Turkey,and other countries of the Middle East [9]. Because variant 2 vaccine is not used in Iran and the current vaccines do not confer complete protection against this virus, the possibility of a wider spread of this variant is high [26].…”
Section: Resultsmentioning
confidence: 99%
“…Varinat 2 viruses are still among the main strains of Jordan, Egypt, Turkey,and other countries of the Middle East [9]. Because variant 2 vaccine is not used in Iran and the current vaccines do not confer complete protection against this virus, the possibility of a wider spread of this variant is high [26].…”
Section: Resultsmentioning
confidence: 99%
“…The essential issue in IBV infection is to protect trachea from virus lesions. The inconvenient situation in the house including high ammonia, dust, CO 2 , and another microorganism in the air would make the condition worse (Habibi et al 2017). In the present study, the vaccinated groups 3 and 4 showed a slight lesion in the trachea in comparison to the no-vaccinated-challenged group.…”
Section: Discussionmentioning
confidence: 99%
“…The threat of IBV infection is global, as this respiratory virus can cause acute and contagious respiratory infections in poultry, resulting in serious economic losses [3, 4]. The strategy of reducing IBV infection through vaccination has been recognised as a viable option to control IBV and has been somewhat successful [5, 6]. The continuing prevalence of IBV might be attributable to divergent IBV subtypes.…”
Section: Introductionmentioning
confidence: 99%